Characterization of the plasma metabolomic profile in infantile epileptic spasms syndrome - Jiang, Lihua; Zhu, Mengying; Zhang, Yi; Yuan, Zhefeng; Gao, Feng (Translational Pediatrics, 2026)
Infantile epileptic spasms syndrome (IESS) represents the most common etiology of epileptic encephalopathy with onset in infancy. It remains unknown whether specific metabolic mechanisms contribute to the pathogenesis of IESS. XXXXXXXXXXX.